A Study on Career Progression of Women during Covid- 19 - A.Manojkumar; Adhithya.V (East Asian Journal of Multidisciplinary Research, 2022)
The COVID-19 pandemic situation is harming the health, social and economic well-being worldwide, and with women at the centre. First and foremost of women are major leading the health response: women structure almost 70% of the health care workforce, exposing them to a greater risk of infection. At an equivalent time, women also are shouldering much of the burden reception, given school and child care facility closures and longstanding gender inequalities in unpaid work. And the women also faced high risks of job and income loss, and face increased risks of violence, and exploitation, abuse or harassment during times of crisis and quarantine. Policy responses must be immediate, which they need to account for women’s concerns. Governments should consider adopting emergency measures to help parents manage work and caring responsibilities, reinforcing and increasing income support measures, expanding support for small businesses and thus the self-employed, and improving measure to assist women victims of violence. Finally, all the rules and policy responses to the crisis must embed a gender lens and account for women’s unique needs, responsibilities and perspectives.